Experiment of Pullout Expansion Anchor in Installation Cast in Place and Post Installed with Concrete Breakout Failure - Huda, Amirul; Apriyatno, Henry (Semarang State University, 2021)
Abstract: The use of anchors in construction is gaining popularity to connect steel and concrete constructions, and to transmit tensile loads acting onto the concrete. This research aims to find out the difference in the strength of anchor based on two methods of installations that are cast in place compared to post installed with the influence of effective depth, diameter of anchor and quality of concrete, and failure of concrete breakout. Expansion anchor used in this study is